A Reading of Article 21 of the United Nations Declaration of Human Rights: Political (Dis)engagement in the Context of Brexit - Ryan Service (Culture e Studi del Sociale)
Free, regular, and open elections are sought-after qualities of a liberal democracy. Reading electoral turnout as an indicator of political engagement, though, is a reductive reading and can obscure entrenched levels of political disengagement. This article considers the implications of Article 21, subsection one, of the United Nations Declaration of Human Rights (1948) as an assessment of political participation. There are three lines of investigation. First, the paper will examine the model of political engagement implied within Article 21 and its subsequent iterations. Second, theories of political participation are linked to a study of civic engagement within the British parliamentary system. Third, building upon these two arguments, the 2016 Brexit referendum is presented as a case study to demonstrate the limitations of a voter turnout measurement. Political participation must be continually (re)imagined, (re)constructed, and reflected upon otherwise we rely upon voting by numbers.